Penterjemahan unsur budaya dalam antologi cerpen Bahasa Korea - Bahasa Melayu perjalanan ke Sam'po / Cho Minsung - Cho, Minsung (2016)
This research discusses the translation strategies and translatability in translating an anthology of Korean and Malay short stories. The process of translation involves two different languages and cultures. The translation process does not only involve a process of transference between languages, but it is also a communication between two different cultures. Therefore, a translator who does not understand the life and culture of the society involved in the translation texts would make mistakes that lead to misunderstanding and offended certain people, providing information or aberrant testimony or completely false information, and even caused an unwanted effect. The first approach used is based on three scholars, Keesing (1958), Newmark (1988) and Katan (2012). The second approach used to analyze the data is based on Venuti's (1995) translation strategies namely domestication and foreignization. The researcher applied Newmark (1988) and Aixelá (1996) procedures. The researcher used questionnnaires parsing the translatibility to explain the approach of domestication translation and foreignization translation. This research analyzed pertains the introduction of translation, literature approach, domestication translation strategy, translatibility and comparison outcome from source texts and target texts. In this research, the researcher found that domestication translation strategy are varied and not only bound to one approach. The choice of Korean and Malaysian domestication translation depends on the existence of domesticated source language in the target language. This research will also contributes new knowledge to translators and also help the people involve in the translation industry